Hospital and Health Insurance Markets Concentration and Inpatient Hospital Transaction Prices in the U.S. Health Care Market. (11th May 2017) - Dauda, Seidu
Abstract : Objective: To examine the effects of hospital and insurer markets concentration on transaction prices for inpatient hospital services. Data Sources: Measures of hospital and insurer markets concentration derived from American Hospital Association and HealthLeaders‐InterStudy data are linked to 2005–2008 inpatient administrative data from Truven Health MarketScan Databases. Study Design: Uses a reduced‐form price equation, controlling for cost and demand shifters and accounting for possible endogeneity of market concentration using instrumental variables (IV) technique. Principal Findings: The findings suggest that greater hospital concentration raises prices, whereas greater insurer concentration depresses prices. A hypothetical merger between two of five equally sized hospitals is estimated to increase hospital prices by about 9 percent ( p < .001). A similar merger of insurers would depress prices by about 15.3 percent ( p < .001). Over the 2003–2008 periods, the estimates imply that hospital consolidation likely raised prices by about 2.6 percent, while insurer consolidation depressed prices by about 10.8 percent. Additional analysis using longer panel data and applying hospital fixed effects confirms the impact of hospital concentration on prices. Conclusion: The findings provide support for strong antitrust enforcement to curb rising hospital service prices and health care costs.